Urgent Stenting of the M2 (Superior) Division of the Middle Cerebral Artery after Systemic Thrombolysis in Acute Stroke - Gupta, R.; Jovin, T.G.; Tayal, A.; Horowitz, M.B. (American Journal of Neuroradiology, 2006)
SUMMARY: We report a case of a 54-year-old man who presented with a right middle cerebral artery territory infarct and was treated with systemic thrombolytics. He continued to fluctuate neurologically and, with the use of angiography, was found to have an occlusion of the right M2 artery (superior division). This occlusion was successfully revascularized with a coronary stent.